2019
DOI: 10.21273/hortsci14018-19
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Cadmium-, Copper-, and Lead-contaminated Soil by Salix mucronata (Synonym Salix safsaf)

Abstract: Phytoremediation is an environmentally friendly and effective method of reducing contaminating ions to very low levels. In this study, the effects of different concentrations of cadmium (Cd), copper (Cu), and lead (Pb) on vegetative growth and the chemical and biochemical compositions of Salix mucronata as well as the potential for phytoextraction of these metals by plant organs were investigated. S. mucronata had the highest survival percentage (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 48 publications
(60 reference statements)
3
14
1
Order By: Relevance
“…To cope with Cd stress, C. olitorius might have undergone the sequestration of Cd in leaf vacuoles, which are metabolically inactive [ 21 ]. A similar increase in translocation factors from roots to shoots was obtained in Salix mucronata exposed to 20–60 mg/kg Cd [ 42 ].…”
Section: Discussionsupporting
confidence: 66%
“…To cope with Cd stress, C. olitorius might have undergone the sequestration of Cd in leaf vacuoles, which are metabolically inactive [ 21 ]. A similar increase in translocation factors from roots to shoots was obtained in Salix mucronata exposed to 20–60 mg/kg Cd [ 42 ].…”
Section: Discussionsupporting
confidence: 66%
“…Hyperaccumulator families, such as Scrophulariaceae, Lamiaceae, Asteraceae, Euphorbiaceae, and Brassicaceae, are essential for this technique. Moreover, some particular plant species, like Celosia argentea [71], Salix mucronata [72], Cassia alata [73], Vigna unguiculata, Solanum melonaena, Momordica charantia [74], Nicotiana tabacum, Kummerowia striata [75], and Swietenia macrophylla [76], may be used as potential plant choices to increase the process of Cd phytoextraction. Moreover, a sub-division of phytoextraction, known as chelate-assisted phytoextraction, is also used as a possible solution for metals that have no hyperaccumulator species.…”
Section: Phytoextractionmentioning
confidence: 99%
“…Melczek et al (2013) showed that tolerance index of biomas or root of S. viminalis was <1 under 3 mM Cu (NO3)2 and at ratios of Ca/Mg (20:1 and 1:10). According to El-Mahrouk et al (2019), the decrement in TIb or TIr of Salix macrunata was increased with increasing the levels of Cd, Cu, and Pb. In general, BCF, TF, and TIb or TIr factors could be used to define Cd, Cu, and Pb hyperaccumulators.…”
Section: Bioconcentration Factor (Bcf) Translocation Factor (Tf %)mentioning
confidence: 99%
“…Overall, foliage elements differ according to their concentrations in soil or soil chemistry and due to the plant species or clones of Salix (Mosseler and Major 2017). According to El-Mahrouk et al (2019), the decrement in N, P, and K % in leaves of Salix mucronata was increased with raising the concentrations of Cd Cl2 (20 to 80 mg/kg soil ), CuCl2 (50 to 200 mg/kg soil), and Pb acetate (250 to 850 mg/kg soil) in the soil.…”
Section: Vegetative Growth and Leaf Chemical Compositionmentioning
confidence: 99%